Incompleteness as a link between obsessive-compulsive personality traits and specific symptom dimensions of obsessive-compulsive disorder - Ecker, Willi; Kupfer, Jochen; Gönner, Sascha (Clinical psychology & psychotherapy, 2014)
This paper examines the contribution of incompleteness/‘not just right experiences’ (NJREs) to an understanding of the relationship between obsessive-compulsive disorder (OCD) and obsessive-compulsive personality traits (OCPTs). It investigates the association of specific OCD symptom dimensions with OCPTs, conceptualized as continuous phenomena that are also observable below the diagnostic threshold. As empirical findings and clinical observation suggest that incompleteness feelings/NJREs may play a significant affective and motivational role for certain OCD subtypes, but also for patients with accentuated OCPTs, we hypothesized that OCPTs are selectively linked with incompleteness-associated OCD symptom dimensions (ordering, checking, hoarding and counting). Moreover, we assumed that this selective relationship cannot be demonstrated any more after statistical control of incompleteness, whereas it is preserved after statistical control of anxiety, depression, pathological worry and harm avoidance. Results from a study with a large clinical sample (n = 185) partially support these hypotheses and suggest that NJREs may be an important connecting link between specific OCD symptom dimensions, in particular ordering and checking, and accentuated OCPTs. Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Message Obsessive-compulsive personality traits (OCPTs) are positively related to obsessive-compulsive disorder symptom dimensions (ordering, checking, hoarding and counting) hypothesized or found to be associated with incompleteness/‘not just right experiences’ (NJREs), but not to washing and obsessions.This positive relationship, which is strongest for ordering and checking, is eliminated when NJREs are statistically controlled.Ordering, checking and accentuated OCPTs may share NJREs as a common affective-motivational underpinning.Dysfunctional behaviour patterns of people with accentuated OCPTs or obsessive-compulsive personality disorder (OCPD) may be viewed as efforts to avoid or reduce subjectively intolerable NJREs.On the basis of such a conceptualization of OCPD as an emotional disorder, a novel treatment approach for OCPD focusing on habituation to NJREs could be developed.
Published online 6 May 2013
Gesehen am 04.09.2020